TI_GERICHTE 15.2012.112 vom 22. Oktober 2012 , Pignoramento di beni che il debitore dichiara essere di proprietà di terzi - TI Tribunale d'appello (2012)
Pignoramento di beni che il debitore dichiara essere di proprietà di terzi